Chatbot System for Mental Health in Bahasa Malaysia - Muhammad Imran Ismael; Nik Nur Wahidah Nik Hashim; Nur Syahirah Mohd Shah; Nur Syuhada Mohd Munir (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2022)
Chatbot has been the driving force of modern communication for business, customer service and even mental healthcare. At the same time, there are not many research and project regarding mental health chatbots in Bahasa Malaysia. This project focuses on developing a chatbot application for mental healthcare in Bahasa Malaysia. This chatbot system is integrated with artificial intelligence and natural language processing. This chatbot utilize the feedforward neural network model to train the datasets. Apart from the backend of the application, Kivy and KivyMD are used to create the app's graphical user interface.